Influence of mechanochemical activation on the features in the of hydration of cement - R. A. Ibragimov; S.I. Pimenov (Инженерно-строительный журнал, 2016)
At the same time with the introduction of various additives to the concrete mix, a promising method for enhancing the physical and mechanical properties of the cement concrete is the activation of the binder. This paper presents the results of the influence of mechanochemical activation of cement slurry on the technological properties of the concrete mix according to GOST 10181-2014 and physico-mechanical properties of heavy concrete. Figures revealed pore structure of heavy concrete, frost resistance, the coefficient of sulphate cement compositions investigated. It is shown that severe frost resistance of concrete prepared mechanochemical activation binder increases 3 times (to mark F600), which is due to a decrease in the total porosity of 39%, decrease capillary porosity 74.8% and the proportion of closed pores increase by 53% in comparison with control composition. X-ray diffraction and differential scanning calorimetry investigated, that the phase composition of cement paste at the age of 1 day, normal-humidity hardening obtained mechano-chemical activation of the binder, is characterized by a high content of calcium hydroxide (Ca (OH)2) (12 %), high content of ettringite (Ca6Al2(SO4)3(OH)12*26H2O) – 13 %, and the lowest content of the initial phases of Portland cement clinker (16%), which causes high physical and mechanical properties of the resulting composite. Production of cement concrete with a high rate of hardening will reduce the holding time of the concrete in the formwork, to reduce or eliminate the heat and humidity treatment, which is relevant in terms of safekeeping energy and resourses.